Destombamentos No Estado De São Paulo Ambiguidades E Transformações Na Atribuição De Valores Aos Bens Culturais - Assis, Bruna Aparecida Silva De [UNIFESP] (2018)
The Presented Research Proposes To Investigate The Subjects Involved In The Denominated "Protection Cancellation" Of A Cultural Property, An Administrative Appeal Which Use Has Increased Recently, Despite Its Exceptional Features. The Aim Is The Understanding, In The Preservation Public Policies Context Of The São Paulo State, Which Are The Reasons And Agents Involved In The Protection Cancellation, How It"S Been Used And Which Are The Problematics It Aggregates, While It Turns The Brazil"S Most Used Legal Instrument Of Property Protection Ineffective. From The Analysis Of Three Case Studies: Igreja De São Gonçalo (São Paulo/Sp), Casa Do Sítio Piraquara (São Paulo/Sp) And Mansão Matarazzo (São Paulo), Belonging, Respectively, To The Three Spheres Of Protection That Act In The São Paulo State, Iphan, Condephaat E Conpresp, This Research Intends To Identify And To Problematize The Main Causes, Discussions And Repercussions Associated To The Protection Cancellation Of A Cultural Property.